(untitled) - Kolman, Bernard (New York, 2009)
This is the International Edition. The content is in English, same as US version but different cover. Please DO NOT buy if you can not accept this difference. Ship from Shanghai China, please allow about 3 weeks on the way to US or Europe. Message me if you have any questions
Lý thuyết đồ thị hữu hạn
Keywords: Computer science; Mathematics